Implementation of Ecommerce on Small and Medium Enterprise - Tugiman Tugiman; Dellih Wijaya; Yakub Yakub (Tech-E, 2021)
The trend of information system development and technological developments is continuously increasing. Every person or business actor must continuously update the technology. Based on the published results of a survey conducted by Indonesian Internet Service Providers Association at the end of 2018, internet users in Indonesia reached 171.17 million from 264.16 million people or 64.8% of the total population.. Related to this, the researchers conducted research on the implementation of e-commerce in Small and Medium Enterprise. Testing of this study uses the User Acceptance Test. The method that the authors do is by making a system that is applied to Small and Medium Enterprise. Untuk mengetahui mengenai penerimaan sistem dan kegunaannya yang berkaitan dengan e-commerce penulis menggunakan metode kuesioner. Based on the black box examiner all test results show valid, while the examiner using the User Acceptance Test produces a number of 80.5% with good criteria. The answers used in this study may be 39 people